Mandala Art Therapy: intervention for individual with Autism Spectrum Disorder (ASD) - Kim, Tae Hoo; Ong, Emelia Ian Li (Penerbit Universiti Kebangsaan Malaysia, 2018)
This study was done to investigate the effectiveness of Mandala Art Therapy (MAT) as a tool to enhance the Social Interaction Skills (SIS) of a student with Autism Spectrum Disorder (ASD). The participant of this study was a student with ASD aged twenty-three years old attending a special development center. There were six sessions of MAT done in this study. The initial score and the after score of participants’ Autism-Spectrum Quotient (AQ) assessment were compared to determine whether there is an improvement of his SIS after going through six sessions of MAT. Besides that, the participant’s behavioral changes and color application from his mandala throughout the six sessions of MAT were also observed and analyzed to explore the improvement of his SIS. After six sessions of observation, the findings obtained from the MAT sessions indicated that MAT is useful to improve the SIS of the participant in this study. This study showed that MAT could be utilized as a useful tool in therapy sessions for other students with ASD to improve their SIS.